Global digital technology convergence : driving diffusion via network effects - Lechman, Ewa; Marszk, Adam (Routledge, 2024)
"Since the 1970s, we have witnessed unprecedented diffusion of digital technologies in both speed and geographic coverage. These technologies are pervasive and disruptive, and lead to profound shifts and transformations in societies and economies. Many claim that emerging network externalities are the principal phenomenon driving the process of technology diffusion and determining its in-time dynamics. This book analyses the unique role network effects play in the process of digital technology diffusion. Using the time span of 1980-2022 and data from over 180 countries, the authors examines the strength and determinates of emerging network externalities in the process of digital technology diffusion across the world. Moreover, using international case studies it traces the process of technology convergence and technology convergence club formation, intending to answer whether cross-country gaps are diminishing or rather growing, and if countries form unique "clubs" within which a rapid convergence occurs. Global Digital Technology Convergence is written for scholars and researchers in the fields of technology and innovation management, ICT, economic development and the economics of innovation"-- Provided by publisher.
Keywords: Information technology -- Economic aspects.; Technological innovations -- Economic aspects.; Diffusion of innovations.; elektronické knihy; electronic books